2018
DOI: 10.1021/acsnano.8b05203
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Transformable, Fusible Rodlike Swimming Liquid Metal Nanomachine

Abstract: The T-1000 liquid metal terminator, which can transform and self-repair, represents a dream for decades that robots can fundamentally change our daily life. Until now, some large-scale liquid metal machines have been developed. However, there is no report on nanoscaled liquid metal machines and their biomedical applications. We describe here a shape-transformable and fusible rodlike swimming liquid metal nanomachine, based on the biocompatible and transformable liquid metal gallium. These nanomachines were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
241
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(271 citation statements)
references
References 46 publications
4
241
1
Order By: Relevance
“…Their self‐propulsion took advantage of the amplitude of the flagellar oscillation induced by an external acoustic field ( Figure A‐i), which enabled control over the micromotor's speed (Figure A‐ii) . Similarly, shape‐transformable nanomachines made of gallium were reported to self‐propel when exposed to an ultrasound field . The micromotors were synthesized by a pressure‐filter‐template method and displayed a rod‐like shape of around 1 cm (Figures B‐i,ii).…”
Section: Externally Driven Nano‐ and Micromotorsmentioning
confidence: 99%
“…Their self‐propulsion took advantage of the amplitude of the flagellar oscillation induced by an external acoustic field ( Figure A‐i), which enabled control over the micromotor's speed (Figure A‐ii) . Similarly, shape‐transformable nanomachines made of gallium were reported to self‐propel when exposed to an ultrasound field . The micromotors were synthesized by a pressure‐filter‐template method and displayed a rod‐like shape of around 1 cm (Figures B‐i,ii).…”
Section: Externally Driven Nano‐ and Micromotorsmentioning
confidence: 99%
“…e) Photothermal treatment of the cancer cell by NIR laser irradiation. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Applications Of Liquid Metal–based Microfluidic Systemsmentioning
confidence: 99%
“…The shape‐transformable and photothermal properties of LMPs could be used as a nanomachine for a medical application. Wang et al synthesized rod shape Ga particles and reported that the particles entered cancer cells through a self‐propelled swim driven by an acoustic radiation force. The injected Ga rods underwent fusion to Ga spheres due to the removal of Ga oxide shell and the Ga spheres killed the cancer cell by photothermal effect under near‐IR light illumination.…”
Section: Applicationmentioning
confidence: 99%